Dank or not? Analyzing and predicting the popularity of memes on Reddit. - Barnes, Kate.; Riesenmy, Tiernon.; Trinh, Minh Duc.; Lleshi, Eli.; Balogh, Nóra.; Molontay, Roland. (Tufts University. Tisch Library., 2021)
Keywords: Memes, Popularity prediction, Machine learning, Sentiment analysis, Image analysis, Content-based analysis, Social media, Visual humor, COVID-19.; Springer Open.